The Effect of Combination of Soy Milk and Calcium in Orthodontic Tooth Movements on Female Rats With Estrogen Deficiency - Ramadhani, Vanda; Narmada, Ida bagus; Hamid, Thalca (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: Orthodontic treatments in elderly patients are influenced by hormonal changes and their effects on the process and prognosis of the treatment. Estrogen deficiency in the post-menopausal period results in bone loss. The process of bone remodeling during Orthodontic treatment for elderly patients is also influenced by the balance of resorption and bone formation processes. Purpose: This study aimed to determine the effect of soymilk combination calcium on orthodontic tooth movement in female rats with estrogen deficiency. Methods: Twenty rats were divided into 5 groups with 4 samples for each group. All samples were performed bilateral ovariectomy. The control group (K) was observed on day 0, P1 group was observed on day 7, P2 group was observed on day 14, P3 group was observed on day 7, and P4 group was observed on day 14. NiTi closed coil spring was placed between the incisor and maxillary molars to move the molars toward the mesial. Osterix and ALP expression were analyzed using SPSS program. Results: The results showed that the highest number of osteoblasts, Osterix and ALP expression was found from the group soy milk and calcium intake in 14 days observation (P4) with a mean ± SD Osterix: 15.75 ± 0.2600, and ALP with a value of 12.60 ± 1,220. Conclusion: Soy milk combination calcium has a very good effect to balance the hormonal condition and bone remodelling for elderly patient or menopause, maintaining bone stability and density during orthodontic treatment.